Tambang dan Perlawanan Rakyat: Studi Kasus Tambang di Manggarai, NTT - Regus, Max (Masyarakat: Jurnal Sosiologi, 2011)
Since a little over a decade ago, Mining Corp. had come to maintain a challenging role in the presence of the host government and local indigenous community, particularly landowners. The reflection of tensions and social complexities have become apparent in Manggarai, Flores, NTT (an exception to many advanced countries with indigenous communities). Mining Corp. did not cultivated a favourable relationship with the indigenous local communities. In other words, they tend to have expansive destruction in local communities. In recent years, global corporations have been speaking the language of development. While corporations are increasingly being imputed a major development role by multilateral organizations, this remains a controversial topic. Even more controversial is the question of whether corporations make a meaningful contribution to development in conflict situations or the absence of democratic government. Some Corp, such as PT Sumber Jaya Asia, do try to justify their operating in Manggarai with some legal basis from local government. This paper contends local resistance through ecocide phenomenon.